Exploring the origins of decreased sound tolerance in tinnitus patients - Kim, Eun Hye; Shin, Seung-Ho; Byun, Sung Wan; Lee, Ho Yun (Frontiers in Neurology, 2023)
This study aimed to confirm the characteristics of auditory function alterations in tinnitus patients with concomitant decreased sound tolerance (ST) and provide insights for developing tailored therapeutic approaches. A retrospective analysis was conducted on patient records from a tertiary university hospital's tinnitus clinic between March 2020 and June 2023. Demographic attributes and audiological profiles were reviewed. Patients were categorized into Group 1 if loudness discomfort level test outcomes were 77 dB or below, measured using an average of frequencies from 250 Hz to 8 kHz. The remaining patients were allocated to Group 2. Among the 434 tinnitus patients, 115 (26.5%) demonstrated decreased ST and were classified as Group 1. This group exhibited higher DPOAE amplitudes (p < 0.001), shortened latency, and decreased threshold of ABR wave V bilaterally (p < 0.05). No significant disparities were observed in gender, age, tinnitus handicap inventory, visual analog scale, and pure-tone audiometry results except subjective hyperacusis. Binary logistic regression analysis utilizing the forward conditional method revealed that the difference between groups was independently linked to DPOAE response at 7277 Hz on the left side (B = 0.093, p < 0.001, EXP(B) = 1.07, 95% CI = 1.044-1.153). Increased DPOAE amplitude and shorter and decreased ABR wave V in tinnitus patients with decreased ST might suggest a possible association with lesions in or around the superior olivary complex or higher central auditory pathway, potentially linked to the inhibition of medial olivocochlear efferents.